Genetic Diversity of Local Rainfed Rice (Oryza Sativa L.) - Siddique, MA; Rashid, ESMH; Khalequzzaman, M; Islam, MZ; Ahmed, MS; Baktiar, MHK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Genetic diversity of 58 traditional local rice genotypes was studied under rainfed condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into nine clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster III contained the highest number of genotypes (13) and the cluster I contained the lowest (2). The highest intra-cluster distance was noticed for the cluster I and the lowest for cluster VII. The highest inter-cluster distance was observed between cluster I and IV followed by cluster IX and IV, cluster I and VI and the lowest between cluster V and III. Regarding inter-cluster distance, the genotypes of cluster IV showed high genetic distance from all other clusters. The genotypes from cluster IV could be hybridized with the genotypes of other characters of other clusters for producing transgressive segregants. Based on positive value of vector 1 and vector 2, flag leaf length, plant height, panicle length and grain breath had maximum contribution towards genetic divergence. The highest cluster means for yield, 1000 grain weight and grain breath were obtained from cluster VIII. The highest plant height, flag leaf width and panicle length were found in cluster II while the lowest mean value for yield, days to flowering and maturity, unfilled grain and the highest mean value for grain length breadth ratio were found in cluster II. Therefore, more emphasis should be given on cluster IV and cluster VIII, cluster I and cluster IV for selecting genotypes as parents for crossing with the genotypes of cluster II which would be used to produce new recombinants with desired traits. Key words: Genetic diversity; D2 analysis; cluster analysis; rice (Oryza sativa L) DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9324 Bangladesh J. Pl. Breed. Genet., 23(2): 41-46, 2010